Prophetic Communication of Spiritual Leaders: An Integrative Framework for Islamic Educational Institutions - Moh. Robi'al Muhasibi; Ainur Rofiiq (Lembaga Yasin AlSys, 2026)
Although prophetic values have been widely discussed in Islamic educational leadership, conceptual explanations of prophetic communication as an observable pattern of institutional communication remain limited. This study aims to develop a conceptual model of prophetic communication that explains the communication patterns of spiritual leaders in Islamic educational institutions. Using a qualitative library research approach, this study examines literature on Islamic leadership, organizational communication, and contemporary communication theories. The findings indicate that prophetic communication functions not merely as a reflection of leaders’ moral character but also as a communicative action pattern that strengthens institutional trust, leadership legitimacy, and organizational commitment. The four prophetic dimensions—shiddiq (truthfulness), amanah (trustworthiness), tabligh (effective communication), and fathanah (wisdom)—operate integratively within organizational communication processes. Based on these findings, this study proposes the Integrative Framework of Prophetic Communication (IFPC), which positions the four prophetic dimensions across three interconnected levels of institutional communication: intrapersonal-spiritual, interpersonal-organizational, and strategic-transformational. The novelty of the IFPC lies in its capacity to conceptualize prophetic communication as an observable and measurable communication pattern, integrate Islamic communication perspectives with contemporary communication theories, and provide an analytical framework applicable to both qualitative and quantitative research. Theoretically, this study enriches the literature on Islamic educational leadership by clarifying the communicative foundations of spiritual leadership. Practically, it offers a value-based framework for leadership development in Islamic educational institutions.